Absence of GATA3/FOXA1 co-expression predicts poor prognosis in upper tract urothelial carcinoma - Wang, Yue; Wang, Yunfan; He, Huiying; Xiong, Yan (Frontiers in Oncology, 2024)
Objective: GATA binding protein 3 (GATA3) and forkhead box A1 (FOXA1) have been individually implicated in the progression of upper tract urothelial carcinoma (UTUC). This study aims to evaluate the prognostic value of GATA3/FOXA1 coexpression in UTUC patients.We collected 108 UTUC pathological tissue samples with complete followup data and 24 normal control urothelial tissues. We created a 132-site microarray and performed immunohistochemistry (IHC) to measure GATA3 and FOXA1 expression levels. Kaplan-Meier survival and Cox regression analyses were conducted to assess UTUC prognosis. Results: GATA3 expression was positively correlated with FOXA1 (P=0.031). Absence of GATA3/FOXA1 co-expression (GATA3-/FOXA1-) was associated with tumor extensive necrosis (P=0.001) after Bonferroni correction for multiple comparisons. GATA3-/FOXA1-was associated with shorter Disease-Free Survival (DFS) (P=0.001) and Cancer-Specific Survival (CSS) (P<0.001) than other combination groups. Multivariate analyses identified extensive necrosis as an independent prognostic factor for CSS (P=0.030). Conclusions: Our study revealed a positive correlation between GATA3 and FOXA1 expression in UTUC. GATA3-/FOXA1-is linked to tumor extensive necrosis and poor prognosis in UTUC and may serve as a potential biomarker for UTUC patients.